Improving the Degree of Teacher Professionalism Through Professional Education - Sahroni Sahroni; Toto Subroto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Teachers' enthusiasm for taking educator certification is still high. This enthusiasm grew because of the recognition of positions as professional educators after passing certification. This article is based on the results of observations of implementing the teacher professional development competency model through PPG Jabatan. This research aims to obtain an overview of the implications of PPG in the Department for teachers' degrees in mastering professional knowledge competencies, professional learning practices, and professional development. This study employs qualitative research methodologies, utilizing the library as the primary information source and additional literature relevant to the paper's thematic focus. Research findings show that PPG demands participants' and managers' ability, sincerity, readiness, and ability. By analyzing the findings of this research, it can be concluded that the Teacher Professional Education (PPG) program can significantly increase teacher professionalism through an in-depth qualitative approach. PPG participants increase their pedagogical knowledge and skills and experience significant growth in self-understanding and reflection abilities. Conclusion PPG increases the mastery of professional knowledge, professional learning practices, and professional development ranging from advanced, decent, and capable to advanced degrees.